2002
DOI: 10.1038/sj.onc.1205594
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin (SGP-2) transient overexpression decreases proliferation rate of SV40-immortalized human prostate epithelial cells by slowing down cell cycle progression

Abstract: Clusterin is a highly conserved, widely distributed glycoprotein whose biological significance is still debated. Involved in many biological processes and disease states, clusterin is induced by cell injury and tissue regression, but is repressed during cell proliferation. We have previously reported that clusterin mRNA induction is associated with epithelial cell atrophy in the rat prostate and both clusterin transcript and protein accumulated in quiescent normal human skin fibroblasts. Here we show that tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
78
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 41 publications
16
78
0
2
Order By: Relevance
“…8,38 In fact, not many studies showed a decrease in sCLU in tumours like that of a proapoptotic. A few reports do, however, suggest decreased sCLU levels in specific cancers, including nonmelanoma skin cancer, 40 oesophageal squamous cell carcinoma, 41 neuroblastoma, 22 prostate, 11,37 and pancreatic cancer 42 (Table 1). In one study, CLU expression was analysed during progression of prostate cancer.…”
Section: Expression Of Clu In Malignant Tumours and Its Potential Rolmentioning
confidence: 99%
See 2 more Smart Citations
“…8,38 In fact, not many studies showed a decrease in sCLU in tumours like that of a proapoptotic. A few reports do, however, suggest decreased sCLU levels in specific cancers, including nonmelanoma skin cancer, 40 oesophageal squamous cell carcinoma, 41 neuroblastoma, 22 prostate, 11,37 and pancreatic cancer 42 (Table 1). In one study, CLU expression was analysed during progression of prostate cancer.…”
Section: Expression Of Clu In Malignant Tumours and Its Potential Rolmentioning
confidence: 99%
“…Furthermore, sCLU confers resistance by some unknown mechanism when overexpressed. 9 The novel therapeutic strategy of silencing sCLU expression to overcome resistance to cancer therapy is of interest for the treatment of cancers that overexpress sCLU as in kidney, 40 k Protein Pancreatic cancer 41 k mRNA Prostate cancer 11,37 k mRNA m * : Increase in expression; k ** : decrease in expression Clusterin in human cancers B Shannan et al prostate, 44 colon, breast, and lung tumours 14 (Table 2). Recent findings support the concept that silencing sCLU expression can enhance the cytotoxicity of various chemotherapeutic agents 1,49 as well as IR.…”
Section: Clu As a Therapeutic Target In Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 We have previously reported that CLU overexpression inhibits cell cycle progression of simian virus 40(SV40)-immortalized human prostate PNT2 and PNT1A epithelial cells. 21 To further assess the role of CLU in apoptotic processes we have studied its expression pattern during the regulation of calcium homeostasis. Ca 2 þ is an important regulator of apoptosis and cell survival.…”
mentioning
confidence: 99%
“…FACS analysis of cell cycle progression was performed as previously described. 21 Values are the mean of cell population (% of total)7S.D. (n ¼ 5).…”
mentioning
confidence: 99%